The 'Adventurers of England' on Hudson bay: a chronicle of the fur trade in the North - Laut, Agnes C. (Agnes Christina), 1871-1936. (Toronto, Glasgow : Brook & company, 1914)
"Bibliographical note": p. 125-128. Mode of access: Internet.